Public Involvement in Budget Transparency in terms of Opportunities and Challenges - Marini Mahyani Nasution; Achmad Lutfi (Jurnal Administrasi Publik (Public Administration Journal), 2022)
The purpose of the article related to public involvement in budget disclosure, known as participatory budgeting, shows more in terms of the opportunities and challenges faced by a decentralized country, where actors in it participate in making decisions through budgeting formulation. This issue is focused on budget transparency not only to encourage public involvement, but public involvement is very necessary for budget transparency. However, this public engagement has its challenges and benefits. This analysis is carried out through literature studies, journals, and related publications. The data were collected through SCOPUS a qualitative. This study concludes that there are several challenges that need to be considered in implementing public involvement in budgeting. Overly complex budgets and inadequate knowledge make this public disinterest a challenge. A conflict occurs when many groups with different interests take part in it. Public involvement is supported because it can increase tax revenue collection and satisfaction in public services and other benefits for social welfare. The results of this analysis will show several challenges and opportunities that use public involvement to be successful in budget formulation so that reforms in the budget can be carried out and can be used as a model for other regions and can become a system of reform in budgeting.